Preliminary study of polyethylene microplastics disrupting energy metabolism, redox balance, and prefrontal cortex structure in Wistar rats - Kehinde, Samuel Abiodun; Abiola, Busola Tolulope; Olajide, Abosede Temitope; Ore, Ayokanmi; Fatokun, Tolulope Peter; Adejumo, Hafsoh Motunrayo; Praveena, Sarva Mangala; Pereira, Mariana Teles; Chusri, Sasitorn; Sasitorn, Chusri (Springer Nature, 2026)
Plastic pollution has become a major environmental and health concern, with microplastics (MPs) increasingly implicated in biological toxicity. This study examined the neurotoxic effects of polyethylene microplastics (PE-MPs) on prefrontal cortex (PFC) bioenergetics, mitochondrial redox balance, and inflammatory responses. Fifteen male Wistar rats were divided into control and treatment groups, receiving oral PE-MP doses (15 or 60 mg/kg body weight) for 28 days. Biochemical assessments revealed significant disruption of PFC bioenergetic enzymes critical for energy metabolism. Oxidative stress and inflammation were evident, characterized by antioxidant depletion, enhanced oxidation, and impaired redox homeostasis. Histological analysis further demonstrated neuronal degeneration, vacuolation, and vascular congestion within the PFC. These findings indicate that PE-MP exposure compromises cortical bioenergetics, disturbs mitochondrial redox equilibrium, triggers inflammatory modulation, and induces structural damage in the rat prefrontal cortex.